Comparative criteria between cultural routes (heritage) and designed routes - Martorell Carreño, Alberto (2017)
The theoretical improvements on an academic issue require developing criteria useful to contrast andcompare different concepts under discussion. In the former issue of Patrimonio Cultural y Turismo (Nº 7,December 2012) we proposed a first approach to this kind of exercise concerning to “cultural routes”concept. In this article we elaborate a more detailed comparative approach, considering the same criteriaproposed to distinguish between cultural routes (or patrimonial routes if we use the terminology used in theOperational Guidelines of the World Heritage Convention) and other kind of routes which are not historic,but designed through different motivations and elements